Hydraulic concrete durability studies with the addition of two industrial byproducts, stone aggregate filler, and foundry sand: A collaborative solution for three large industries - Guilliana Agudelo; Carlos A. Palacio; Sergio Neves Monteiro; Henry A. Colorado (Cleaner Materials)
This research investigates the use of two industrial byproducts added to hydraulic concrete and their impact on its durability when metakaolin is added. The byproducts used were a stone aggregate filler from the production of asphalt concrete, and foundry sand. The environmental impact of this development is significant as it involves three large industries that collaborated for the study: concrete, metal casting, and aggregate mining, quite economically influential elsewhere but particularly in developing countries. The stone aggregate was obtained after a drying and preheating process of the stone aggregates to produce asphalt, while the foundry sand is obtained after iron smelting. The effectiveness of the additions in mortar bars was tested by the expansion measurements conducted at 25 °C. This study also aims to determine how the additions affect the expansion and the alkali-silica reaction, which could increase the concretés durability. It was found that both byproducts can be classified as type N pozzolans and that achieve an expansion reduction of 32.9 % with the aggregate filler; of 36.84 % with the foundry sand; and of 71 % with the metakaolin. The microstructure of samples was evaluated via XRD and SEM over the samples immersed in NaOH during 18 days, revealing phases such as portlandite, oligoclase, quartz, cordierite, calcite, coesite, biotite, and albite. The SEM showed some of these phases as well as, in addition to the ASR-gel (alkali-silica reaction) as a rosette around aggregates. It was found the ASR gel in all the mortars evaluated. Last, one important outcome is that this investigation was conducted as a University-Industry collaboration, enabling a real green solution for the wastes.